2018
DOI: 10.5653/cerm.2018.45.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chromatin and DNA integrity, methyltransferase mRNA levels, and global DNA methylation in oligoasthenoteratozoospermia

Abstract: ObjectiveTo investigate sperm chromatin/DNA integrity, global DNA methylation, and DNMT mRNA transcription in men with oligoasthenoteratozoospermia (OAT) compared with normozoospermic men.MethodsSemen samples from 32 OAT patients who comprised the case group and 32 normozoospermic men who comprised the control group were isolated and purified using a standard gradient isolation procedure according to World Health Organization criteria. DNMT1, DNMT3A, and DNMT3B transcripts were then compared between groups usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
(50 reference statements)
0
19
0
2
Order By: Relevance
“…), in addition to significant changes in both histone modification and DNA methylation status (Rahiminia et al . ). Therefore, disruption of the testicular epigenetic status in F1 male offspring could provide one mechanism through which paternal transgenerational programming occurs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), in addition to significant changes in both histone modification and DNA methylation status (Rahiminia et al . ). Therefore, disruption of the testicular epigenetic status in F1 male offspring could provide one mechanism through which paternal transgenerational programming occurs.…”
Section: Discussionmentioning
confidence: 97%
“…N 6 -adenosine methylation (m 6 A) is the most prevalent modification to mammalian RNA and is regulated by a series of methyltransferases and demethylases (Yue et al 2015). In humans, increased expression of FTO, METTL3 and METTL14, as well as levels of m 6 A, have been identified in the sperm of infertile men (Yang et al 2016), in addition to significant changes in both histone modification and DNA methylation status (Rahiminia et al 2018). Therefore, disruption of the testicular epigenetic status in F1 male offspring could provide one mechanism through which paternal transgenerational programming occurs.…”
Section: Paternal Diet Alters F1 Testicular Epigenetic Statusmentioning
confidence: 99%
“…It is thought that semen parameters do not directly represent the status of sperm nuclei, as sperm with normal motility and morphology may have chromatin and/or DNA abnormalities [34]. Previous studies have found significant positive correlations between DNA fragmentation and CMA3 positivity in infertile men [27,28,35]. Moreover, protamine defects were associated with the fertilization rate in stimulated assisted reproduction cycles according to Bianchi et al [36] and Iranpour et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…All types of cells have their own epigenetic profiles, 10 and the epigenetic profile of germ cells is even more special as it can be transferred to further generations 11 . Along with the aspect of transgenerational inheritance, the epigenetic status of spermatozoa is an important factor in fertility because recent studies have shown that spermatozoal DNA methylation patterns can be correlated with sperm quality 12 . Consequently, this can affect the outcome of in vitro fertilization (IVF) procedures in terms of abnormal embryogenesis and pregnancy rates 13,14 .…”
Section: Introductionmentioning
confidence: 99%